Оценка ущерба от абразионных риск-процессов на водных объектах Республики Беларусь - Levkevich Виктор; Kobyak Валерий; Pastukhov Сергей; Kukshinov Михаил; Buzuk Александр (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2008)
We presented here the method for assessment of the abrasion damage on the tanks of the Republic of Belarus.